Compartimentação do relevo no hemigráben do Tacutu, Estado de Roraima - Falcão, Márcia Teixeira (2007)
The sedimentary basin of the Tacutu is located in the state of Roraima, Brazil. It is an implanted distensive segment in the Mesozóic (upper Jurassic - lower Cretaceo). It is an half-graben incased in the Shield of the Guianas, prolongated in the northeast direction - southwestern, with about 300 km of length varying 30 the 50 width km, extending itself of the Republic of Guyana to the capital of the state of Roraima, Boa Vista. The half-graben was implanted in a zone of reactivation of the Belt of Central Guyana. The dynamics and evolution of the relief forms are conditioned by the result of successive periods of training in which it has as influence the tectonics processes and the external agents what vary throughout the time and they can be found in the evidences of the basin Tacutu, becoming thus an atypical area in the territory. We consideration the data already concerning the area in study and diverse research to understand the evolution of the process. The approach about the geomorphological compartimentation of graben of Tacutu using techniques of the Geographic Data Sistem by means of applicatory ArcGis 9.1. that favored the construction of a digital model of the land. They were delineated the curves of levels and the nets of drainings based on letters 1:100.000, which procedure disclosed an evident control of the draining suggesting the geomorphology of the searched area is controlled for normal imperfections NE-SW and for neotectonics activities compartimentments NW, being evidenced mainly in the rivers Arraia and Tacutu, and that they are ties the process of sedimentation of the Boa Vista Formation. The geomorphological compartimentation of the area is characterized through three main compartments: the Planície Amazônica, evidenced for being a plain area wich strechs itself for bands lightly prolongated deposited for the rivers arenaceous, argillaceous and conglomerates, recent sediments unconsolidated in general associates to the deposits of the Quaternary, mainly in the Holocene, of fluvial origin; the Boa Vista Depression represented for a planing surface,formed on pre-Cambrian and Phanerozoic rocks and the Residual Plateaus, divided in: Volcanic Residual, represented for the Apoteri Domain, Residual Sedimentary represented for the Tucano Montain range and the Residual of the Proterozoic that they are remainders that demonstrate the evolution of the regional relief, probably since the installation of the followed basin of its inversion, and the dissection of these residuals throughout the cenozoics times. The evolution process of this basin sedimentary was conditional the successive occurred climatic oscillations in the region during the Quaternary, that can be observed in the lines of rocks, as well as in the draining net, and still the presence of normal and transcorrentes imperfections, characteristic these that they had corroborated for the evolutive confirmation of the neotectonic picture of the basin.